ChemInform Abstract: Synthesis of N‐Benzothiazol‐2‐yl‐amides by an Iron‐Catalyzed Oxidative C(sp2)—H Functionalization. Issue 10 (March 2015) - Wang, Junke; Zong, Yingxiao; Zhang, Xuexin; Gao, Yang; Li, Zhengliang; Yue, Guoren; Quan, Zhengjun; Wang, Xicun
Abstract In contrast to the cyclization of 1‐acetyl‐3‐arylthioureas, 1‐benzoyl‐arylthioureas form complex reaction mixtures.